2008
DOI: 10.1111/j.1442-2050.2007.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and pathological evidence of response to neoadjuvant therapy in adenocarcinoma of the esophagus

Abstract: Our aim was to determine if fluorodeoxyglucose positron emission tomography (FDG-PET) could be correlated with a pathological response in patients with esophageal adenocarcinoma receiving neoadjuvant chemotherapy and/or chemoradiation therapy. Patients with resectable, histologically proven adenocarcinoma of the esophagus were entered in the study. Preoperative chemotherapy comprised two cycles of cisplatin and 5-fluorouracil. Radiation therapy commenced with the second cycle on day 22. FDG-PET images were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 38 publications
(106 reference statements)
1
38
0
Order By: Relevance
“…Irrespective of whether chemotherapy or chemoradiotherapy was given, change in SUV was unable to distinguish pathological responders from non responders, although this may be influenced by the limited number of responders (n=1 chemotherapy, n=6 chemoradiotherapy). This however reflects realistic response rates to neoadjuvant therapies [3].…”
Section: Predicting Pathological Responsementioning
confidence: 99%
See 3 more Smart Citations
“…Irrespective of whether chemotherapy or chemoradiotherapy was given, change in SUV was unable to distinguish pathological responders from non responders, although this may be influenced by the limited number of responders (n=1 chemotherapy, n=6 chemoradiotherapy). This however reflects realistic response rates to neoadjuvant therapies [3].…”
Section: Predicting Pathological Responsementioning
confidence: 99%
“…The differences between the studies may be in part explained by differing tumour types, tumour locations and neoadjuvant therapy and [43] demonstrated that a complete metabolic response did not equate to a complete pathological response. Smithers et al [3] looked at both neoadjuvant chemotherapy and chemoradiotherapy in adenocarcinomas of the oesophagus and GOJ with PET performed three to six weeks post completion of therapy. Irrespective of whether chemotherapy or chemoradiotherapy was given, change in SUV was unable to distinguish pathological responders from non responders, although this may be influenced by the limited number of responders (n=1 chemotherapy, n=6 chemoradiotherapy).…”
Section: Predicting Pathological Responsementioning
confidence: 99%
See 2 more Smart Citations
“…It must be underlined that other authors [8][9][10] were already critical of the use of 18 F-FDG PET in making important clinical decisions on patient treatments.…”
mentioning
confidence: 99%